Mycobacterium avium lysate induces matrix metalloproteinase-1 in intestinal tissue and peripheral blood: Observations from selected hospital based Zambian adults. (June 2018) - Chongwe, Gershom; Michelo, Charles; Sinkala, Edford; Kayamba, Violet; Nzayisenga, Jean-Baptiste; Drobniewski, Francis; Kelly, Paul
Highlights: Mycobacterium avium could remodel the mucosa and lead to environmental enteropathy. M. avium induced the secretion of MMP-1 in duodenal tissue and whole blood. M. avium also induced the secretion of IL-1β and IL-6 in duodenal tissue. Abstract: Objectives: Environmental enteropathy is prevalent in low-income countries, although its aetiology is unknown. We investigated if Mycobacterium avium antigens, which are commonly found in the environment, could contribute to its pathogenesis in a population known to have widespread environmental enteropathy. Methods: Routine endoscopy patients at the University Teaching Hospital, Lusaka whose endoscopy results were normal submitted duodenal biopsies and whole blood samples. Samples were stimulated with M. avium lysate over 24 h while unstimulated samples served as negative controls. Matrix metalloproteinase (MMP) and cytokine response in supernatants were quantified using ELISA and cytometric bead array. Results: Samples from 48 patients (56% women) were analysed, with a median age of 35 years (IQR 27.5, 50.5). M. avium induced the secretion of a wide-range of Th1, Th2 and Th17 cytokines in blood but only IL-1β and IL-6 in duodenal tissue. However it differentially induced the secretion of MMP-1 in duodenal tissue compared to negative controls (p = 0.004). A similar MMP-1 response but with lower concentrations was observed in blood. Conclusion: The induction of MMP-1 and cytokines by M. avium in duodenal tissue suggests that environmental mycobacteria could contribute to the epithelial disruption seen in environmental enteropathy, and a need to further explore possible biomarkers that may predict this exposure in at-risk populations.